1972
DOI: 10.1007/bf01852214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of respiratory acidosis on heart and circulation in cats, pigs, dogs and rabbits

Abstract: In closed chest cats, dogs, rabbits and pigs, anaesthetized with pentobarbital and relaxed with diallylnortoxiferinium dichloride the effects of a respiratory acidosis on heart and circulation as well as their reaction to sympathomimetic amines were studied.1. In cats and pigs a respiratory acidosis causes a rise of frequency, dp/dtmax of the left ventricle and systolic blood-pressure. In rabbits an acidosis causes no significant alteration of blood-pressure and dp/dtmax. In dogs frequency, dp/dtmax and blood-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…One study reported a change towards hyponatremia in dogs, but without significance, in response to hemodynamic instability [1]. As regard to iMg level, the findings were compatible with the study carried out by Kohler et al in which was demonstrated that mobilization of magnesium from body tissues takes place if body pH is altered [14].…”
Section: Discussionsupporting
confidence: 84%
“…One study reported a change towards hyponatremia in dogs, but without significance, in response to hemodynamic instability [1]. As regard to iMg level, the findings were compatible with the study carried out by Kohler et al in which was demonstrated that mobilization of magnesium from body tissues takes place if body pH is altered [14].…”
Section: Discussionsupporting
confidence: 84%
“…Previous investigators have measured increased circulating catecholamines during acute hypercapnic acidosis (Morris and Miller, 1962;Tenney, 1956), although Kohler et al (1972) observed unchanged plasma norepinephrine and epinephrine concentrations during acute hypercapnic acidosis in anesthetized dogs. The unchanged myocardial response to isoproterenol infusion during hypercapnic acidosis differs from past studies, which have observed diminished responsiveness to isoproterenol during acute hypercapnic acidosis (Page and Olmstead, 1951;Tenney, 1956;Atkinson and Rand, 1972).…”
Section: Discussionmentioning
confidence: 97%